Can resources save rationality? "Anti-Bayesian" updating in cognition and perception. (11th March 2020) - Mandelbaum, Eric; Won, Isabel; Gross, Steven; Firestone, Chaz
Abstract: Resource rationality may explain suboptimal patterns of reasoning; but what of "anti-Bayesian" effects where the mind updates in a direction opposite the one it should? We present two phenomena – belief polarization and the size-weight illusion – that are not obviously explained by performance- or resource-based constraints, nor by the authors' brief discussion of reference repulsion. Can resource rationality accommodate them?